2012
DOI: 10.1177/0148607112440120
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of ω‐3 Fish Oil Lipid Emulsion Combined With Parenteral Nutrition on Patients Undergoing Liver Transplantation

Abstract: Posttransplant PN support can greatly improve metabolism of protein and nutrition states of patients. ω-3 fatty acid-supplemented PN significantly reduces injury of the transplanted liver, decreases the incidence of infectious morbidities, and shortens posttransplant hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 19 publications
0
45
0
7
Order By: Relevance
“…In clinical practice, the administration of a fish oil lipid emulsion combined with parenteral nutrition has been shown to decrease the incidence of infectious morbidities following orthotopic liver transplantation [18]. In another study, a significantly lower rate of infections, fewer complications, and a shorter length of hospital stay was demonstrated in a group of 230 postsurgical patients who received parenteral nutrition including fish oil for at least 3 days [19].…”
Section: Omega-3 Polyunsaturated Fatty Acid-supplemented Nutritionmentioning
confidence: 98%
“…In clinical practice, the administration of a fish oil lipid emulsion combined with parenteral nutrition has been shown to decrease the incidence of infectious morbidities following orthotopic liver transplantation [18]. In another study, a significantly lower rate of infections, fewer complications, and a shorter length of hospital stay was demonstrated in a group of 230 postsurgical patients who received parenteral nutrition including fish oil for at least 3 days [19].…”
Section: Omega-3 Polyunsaturated Fatty Acid-supplemented Nutritionmentioning
confidence: 98%
“…Three trials, including one identified after the systematic review was published [4], addressed the use of parenteral nutrition after transplantation. No effect of the intervention was observed with regard to mortality or serum bilirubin [2 && ].…”
Section: Liver Transplantationmentioning
confidence: 99%
“…Association may be caused by other confounding factors; for example, malnourished patients may simply have more severe disease. A subsequent search in August 2013 identified three additional RCTs [4][5][6]. This paper will review the RCTs that have been reported to date that have assessed the utility of various nutritional interventions [parenteral nutrition, enteral nutrition, or nutritional supplements (containing at least a source of nitrogen and nonprotein calories)] in patients with liver disease.…”
Section: Introductionmentioning
confidence: 99%
“…It may also decrease the incidence of rejection, but the mechanisms involved remain unknown [27,28]. Supplementation of omega-3 FA may also reduce occurrence of new-onset diabetes mellitus [29], reduce infectious morbidities, and shorten post-transplantation hospital stays [21,30].…”
Section: Discussionmentioning
confidence: 99%